Late orogenic extension in Hellenides - ΚΙΛΙΑΣ Α. (Bulletin of the Geological Society of Greece, 2001)
In the Hellenic orogen both typs of late orogenic extension, associated with deep crustal parts exhumation, are recognized during the Tertiare: In the areas of Olympos-Ossa and Pelion Mts in Northern Greece, as well as in the island of Crete in Southern Greece a bivergent late orogenic extension is recognized. Nappes collapse took place immediately above the cold accretionary wedge while compression was active at depth. Heer high pressure assemplages were good preserved. On the contrary, in the Rhodope and Cyclades areas an asymmetric extension dominates. Heer extensional exhumation of deep crustal rocks took place in the high thermal flow back-arc region and high pressure metamorphic rocks were highly overprinted by greenschist to amphibolite facies metamorphism. Partial melting and granitoids intrusions followed the high grade metamorphic reworking of the rocks. Tertiary late orogenic extension in the Hellenides tooke place simultaneously with successive subductions processes and crustal thickening at the front of the extended plate, forming with the associated compression a SW-ward migrated system. Extension started in the Rhodope massif during the Eocene/Oligocene to be reached in the Olympos, Ossa, Pilion and Cyclades areas in the Oligocene/Miocene and final in the Crete island at the more external Hellenides, during the Mid-Miocene. Changes in the rate of convergence between Africa and Eurasia associated with retreating plate boundaries conditions allowed the successive, extensional exhumation of the deep crustal rocks in the Hellenides. Assymetric collapse in the back-arc area was possibly favoured, because the high potential energy of the thickened crust in the active orogenic arc was counteracted by the continuing subduction along the boundaries of the converging segments of Africa and Eurasia. Symmetric collapse of the overthickened crust above the cold accretionary prism was favoured probably, due to an increasing of the upward pressure produced by the unterplating of the lithospheric slap beneath the accretionary wedge.